The Impact of Organizational Culture and Self-Efficacy on Employee Performance: The Mediating Role of Work Motivation - Adawiyah, Haura; Herdiyana, Herdiyana (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
This study aims to analyze the influence of organizational culture and self-efficacy on employee performance, with work motivation serving as an intervening variable. The research was conducted at the Public Works and Public Housing Office (PUPR) of Bogor City, which plays a strategic role in implementing public infrastructure development and service programs. The study adopts a quantitative explanatory approach using survey methods with a sample of PUPR employees selected through proportional sampling techniques. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect effects. The results reveal that organizational culture and self-efficacy have significant positive effects on work motivation and employee performance. Moreover, work motivation partially mediates the relationship between the two independent variables and employee performance. These findings indicate that a strong organizational culture characterized by collaboration, integrity, and innovation combined with high employee self-efficacy enhances motivation and leads to improved work outcomes. The study contributes theoretically by integrating motivational and behavioral frameworks in the public sector context and provides managerial implications for strengthening organizational culture and empowerment programs to optimize civil servant performance in regional government institutions.